Pyridylnidulin exerts anti-diabetic properties and improves non-alcoholic fatty liver disease in diet-induced obesity mice - Likitnukul, Sutharinee; Tepaarmorndech, Surapun; Kaewamatawong, Theerayuth; Yangchum, Arunrat; Duangtha, Chanathip; Jongjang, Pimrapat; Mangmool, Supachoke; Pinthong, Darawan; Isaka, Masahiko (Frontiers in Molecular Biosciences, 2023)
Non-alcoholic fatty liver disease (NAFLD) is one of the metabolic disorders related to the pathophysiology of type 2 diabetes mellitus (T2DM). Therapeutic strategies are focused on the improvement of energy balance and lifestyle modification. Additionally, the derivative of the bioactive fungal metabolite is of interest to provide health benefits, especially in obese and pre-diabetic conditions. In our screening anti-diabetic compounds from fungal metabolites and semisynthetic derivatives, a depsidone derivative, namely pyridylnidulin (PN), showed potent glucose uptake inducing activity. The present study aimed to investigate the liver lipid metabolism and anti-diabetic properties of PN. Male C57BL/6 mice were induced obesity and pre-diabetic conditions by dietary intervention with a high-fat diet (HFD) for 6 weeks. These obese mice were orally administered with PN (40 or 120 mg/kg), metformin (150 mg/kg), or vehicle for 4 weeks. Improved glucose tolerance and reduced fasting blood glucose levels were found in the PN and metformin-treated mice. Additionally, hepatic triglyceride levels were consistent with the histopathological steatosis score regarding hepatocellular hypertrophy in the PN and metformin groups. The levels of plasma adipocytokines such as tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1 (MCP-1) were reduced in the PN (120 mg/kg) and metformin-treated mice. In addition, hepatic gene expression involved in lipid metabolism, including lipogenic enzymes was significantly reduced in the PN (120 mg/kg) and metformin-treated mice. The increased protein expression levels of phosphorylated AMP-activated protein kinase (AMPK) in PN and metformin-treated mice were revealed as the underlying mechanisms to improve metabolic parameters. These results suggested that PN provided the health benefit to slow the progression of NAFLD and T2DM in obese and pre-diabetic conditions.